An Analysis On The Suitability Of The English Textbook"Pathway To English" For The Tenth Grade Students OfSenior High School Based On Tomlinson's Theory - Subariyah, Subariyah, Drs.Djoko Srijono, M. Hum, Dr.Dwi Haryanti, M.Hum (2014)
This research paper aims at finding out whether the English textbook entitled "Pathway to English" for the tenth grade students of Senior High School is suitable with good criteria of English textbook proposed by Tomlinson and the Scientific Approach of the 2013 Curriculum or not. The writer applies descriptive study as the type of this research. The data are collected by using content analysis technique. The data in this study are the materials in the English textbook "Pathway to English". The writer uses descriptive analysis as the technique for analyzing data, the steps are: (1) defining criteria, (2) subjective analysis, (3) objective analysis, and (4) matching. The result of this study shows that the English textbook "Pathway to English" fulfills 81,25% of Tomlinson's theory and caters 100% of the Scientific Approach of the 2013 Curriculum. It means that the English textbook "Pathway to English" is a very suitable textbook for the tenth grade students who implement the 2013 Curriculum in their school.